On the Evolutionary History of a Simulated Disk Galaxy as Seen by Phylogenetic Trees - Rojas-Arriagada, A (Institute of Physics, 2024)
Phylogenetic methods have long been used in biology and more recently have been extended to other fields—for example, linguistics and technology—to study evolutionary histories. Galaxies also have an evolutionary history and fall within this broad phylogenetic framework. Under the hypothesis that chemical abundances can be used as a proxy for the interstellar medium’s DNA, phylogenetic methods allow us to reconstruct hierarchical similarities and differences among stars—essentially, a tree of evolutionary relationships and thus history. In this work, we apply phylogenetic methods to a simulated disk galaxy obtained with a chemodynamical code to test the approach. We found that at least 100 stellar particles are required to reliably portray the evolutionary history of a selected stellar population in this simulation, and that the overall evolutionary history is reliably preserved when the typical uncertainties in the chemical abundances are smaller than 0.08 dex. The results show that the shapes of the trees are strongly affected by the age-metallicity relation, as well as the star formation history of the galaxy. We found that regions with low star formation rates produce shorter trees than regions with high star formation rates. Our analysis demonstrates that phylogenetic methods can shed light on the process of galaxy evolution. © 2024. The Author(s). Published by the American Astronomical Society.